Comparison of the Burrowing Ability of Different Groups of Manila Clams (Ruditapes philippinarum) - Xiang Li; Jianing Wang; Zelin Zhang; Jin Wen; Yu Li; Haoyang Zhang; Pan Lu; Lei Chen (Biology)
Clams from the Fujian group, the Laizhou group, and the zebra strain group were used in this investigation; their shell lengths were 1.0 cm, 1.5 cm, and 2.0 cm, respectively. Tests were conducted on substrates with particle sizes ranging from 151 to 180 µm, 181 to 250 µm, 251 to 425 µm, and 426 to 850 µm. Both centralized and decentralized sowing modes were used. According to the findings, the clams with the 1.0 cm shell length had the highest burrowing rate and the lowest ET50. From 0 to 120 min, the burrowing rate of the zebra strain group was higher than that of the other groups. Clams with shell lengths of 1.0 cm and 1.5 cm had similar burrowing rates at the end of the test, with the zebra strain group having the highest burrowing rate. Manila clams burrowed more quickly when the substrate’s particle sizes were between 181 and 425 µm. The clam burrowing rates in the decentralized sowing mode were high during the first 20 min of the test, but at the end of the test, there was no significant difference between the two sowing modes (p > 0.05). In summary, there were differences in the burrowing ability among the three groups. The clams with a shell length of 1.0 cm in the three groups had a higher burrowing efficiency, and the decentralized sowing mode was more conducive to the clams quickly burrowing into the substrate.